STRATEGI MANAJEMEN PEMASARAN LEMBAGA PENDIDIKAN ISLAM DI MTS MADINATUL ILMI DESA LUBUK KERTANG KECAMATAN BERANDAN BARAT - Siti Mariani, Ahmad Fuadi, Muhammad Saleh (Pusdikra Publishing, 2020)
Interesting events occur in the administration of education, especially during the acceptance of new students. The community seems to have understood that madrasas are suitable for sending their sons/daughter to school, for them the criteria for madrasas that have a good image are madrasas that have succeeded in satisfying users of educational services. The focus of this research are: 1) How is the strategy of educational services in improving the image of Islamic educational institutions at MTs Madinatul Ilmi? 2) How is the marketing management strategy of Islamic educational institutions at MTs Madinatul Ilmi? 3) How is the impact of the marketing management strategy of Islamic educational institutions at MTs Madinatul Ilmi for the community?. This research includes qualitative research, the type of case study with a multi-case design. The data collection process used the method of observation, in-depth interviews and documentation. Data analysis used the Miles and Huberman model, the data collected and checked for validity were analyzed by means of date reduction, data presentation and conclusion drawing. Checking the data using the triangulaton method. While the result of this study are: First, Educational services at MTs Madinatul Ilmi prioritize efforts to fulfill customer expectations and satisfaction, this is indicated bay 3 things, namely satisfaction with academic quality services, satisfaction with standardization of teachers and madrasas administrative staff and quality satisfaction of graduates. Second, The marketing strategy in improving the image is carried out by several strategy, and financing strategy. However, an effective strategy at MTs Madinatul Ilmi is to show evidence of the quality of graduates and build an image of service satisfaction through word of mouth. Third, The impact of the marketing strategy and its implications for imaging at MTs Madinatul Ilmi are high customer loyalty for education service users, stronger public trust, community support and effective collaboration between madrasas and parent.